Development and validation of the multidimensional impacts of movement scale (MIMS) for yoga, weightlifting, and running - Lynn, Sarah; Basso, Julia C. (Frontiers in Psychology, 2023)
Background Movement is an essential element in maintaining overall well-being, producing both physical and mental health benefits. Yoga is a mindful movement practice, with traditional yogic texts providing a framework, called the Koshas, that delineates how an intentional movement practice may impact multidimensional aspects of an individual. To date, no self-report measure examines the multifaceted ways that movement affects the individual at a physical and psychological level. Therefore, we developed the Multidimensional Impacts of Movement Scale (MIMS) by aligning ancient yogic traditions with current neuroscientific concepts. Methods MIMS was developed based on the five categories of the Koshas; 9 questions per Kosha resulted in 45 total questions. Participants (n = 103) self-identified as having yoga, running, or weightlifting as their primary movement practice, engaging in this practice at least 30 min per session, once a week, for the past 3 months. Participants engaged in their usual movement practice and then (within 2 h of their workout session) completed the MIMS along with a series of previously validated questionnaires. After a period of 2 weeks, participants completed their normal movement practice once again and took the MIMS a second time to assess test–retest reliability and Cronbach’s alpha. Validity testing included convergent and divergent validity testing through Pearson’s product-moment correlations and confirmatory factor analysis. Results One-hundred and three participants completed all study measures. Test–retest reliability demonstrated stability over time (r = 0.737, p < 0.001). Cronbach’s alpha was between 0.775 and 0.840 for each of the factors, p < 0.001. MIMS was sensitive to confirmatory and discriminatory validity testing. Validity was also demonstrated through confirmatory factor analysis (i.e., Chi Square, Comparative Fit Index, Root Mean Square Error of Approximation). Conclusion MIMS is a valid and reliable tool to measure the multidimensional impacts of movement. The tool provides information about the effects of movement on a range of physical and psychological elements including subscales representing the body, energy, mind, intuition, and contentment. Physical activities that include aspects of mindfulness may demonstrate the most robust effects on the MIMS.